Process model of development of adolescents’ social initiative in educational organization environment - Svyatoslav V. Beloklokov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents theoretical and methodological grounds that actualize the development of a process model of development of adolescents social initiative in educational organization environment as a regulatory of productive stimulation of civil, patriotic, spiritual and moral development of young people, the basis for creative activity in a changing reality, for conscious opposition to the destructive influences of risky society. The problems and risks of insufficient attention to the development of adolescents social initiative in school by means of the opportunities of the educational environment have been identified. The content of the basic concepts of research is specified on the basis of interdisciplinary analysis of literature and advanced pedagogical experience. A designed process model of the development of adolescents social initiative in the educational organization environment is presented. Its block structure (target, methodological, content, productive blocks), optimally implemented in the sequence of stages (orienting, activating, reflexive) is described. The research also characterizes the target block of the model which sets guidelines for updating the study based on the social order of society, the requirements of regulatory legal documents in the field of education and the social sphere. The methodological block of the model was substantiated, reflecting the conceptual ideas of the environmental and activity scientific approaches and the general scientific principles arising from them (axiology, individuality and personal priorities, social cooperation, eventuality). The content block is aimed at the phased implementation of organizational forms and methods of the process model of the development of adolescents social initiative from the standpoint of using the capabilities of the educational organization environment (semantic, informational, activating) and its components (value-regulatory, informational, communicative, event, spatial). A productive block of the model has feedback functions and makes it possible to determine the productivity of the conducted study in the context of the sequential transition of the level of the components development of the adolescents social initiative (eposeological, axiological, praxeological) from low to medium and high.